Influence of water content, concentration, and nutrient addition on the biofiltration of toluene for air pollution mitigation using soil biofilters with water content control - Badilla, Daisy B.
In this study on biofiltration as an air pollution control technology, three laboratory-scale biofilters with water content control were used to treat toluene-contaminated air with soil as the biofilter bed medium. The microorganisms in the biofilter medium degrade and convert the toluene to water, carbon dioxide, and biomass. Thus, biofiltration is often favored over other air pollution control technologies since it does not produce secondary pollutants. It also does not involve expensive maintenance and operating costs. However, one of its disadvantages is the problem on water content control.